2023
DOI: 10.1590/s1677-5538.ibju.2023.0101
|View full text |Cite
|
Sign up to set email alerts
|

Treating asthma in patients with enuresis: repercussions on urinary symptoms

Patricia Dahan,
Pricila Mara Novais de Oliveira,
Aparecida Regina Brum
et al.

Abstract: Background: Children presenting enuresis are more likely to be asthmatics. The association between enuresis and sleep-disordered breathing has already been demonstrated and several studies have shown at least partial improvement of two thirds or more of the cases of enuresis adenoidectomy. Studies have already described associations between enuresis and allergies but do not assess the repercussions of allergy treatment in enuretics. Objective: This study aims to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It is a known fact that there is a connection between airway obstruction and enuresis. The association between nocturnal enuresis and upper airway obstruction due to allergic rhinitis or obstructive sleep apnea has already been documented (1)(2)(3)(4)(5)(6)(7). We designed our study to reveal the relationship between incontinence/enuresis and allergic diseases such as asthma and/or allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a known fact that there is a connection between airway obstruction and enuresis. The association between nocturnal enuresis and upper airway obstruction due to allergic rhinitis or obstructive sleep apnea has already been documented (1)(2)(3)(4)(5)(6)(7). We designed our study to reveal the relationship between incontinence/enuresis and allergic diseases such as asthma and/or allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional voiding or voiding dysfunction can be briefly defined as having problems with storing the urine in the bladder or emptying the bladder or both. The frequency of monosymptomatic enuresis is found to be increased among pediatric patients with allergic diseases, and there are certain studies demonstrating the relationship between nocturnal enuresis and asthma (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr. Dahan and collegues form Brazil performed on page 590 ( 4 ) an interesting study about the asthma treatment in patients with enuresis: and the repercussions on urinary symptoms and concluded that controlling asthma in children with primary enuresis resulted in a significant increase in dry nights.…”
mentioning
confidence: 99%